Knowledge and Practice of Biomedical Waste Management among Nurses at a Tertiary Level Hospital in Bangladesh - Akbor, Jahanara; Rani Mallick, Dipali; Jahan, Ferdous; Khatun, Shanzida; Singha, Radha (Nursing and Health Sciences Journal (NHSJ), 2024)
Biomedical waste (BMW) poses significant health risks due to its potential to spread infections and environmental harm. Effective management is crucial to mitigate these risks. This study aimed to assess the knowledge and practices of senior nurses at a tertiary hospital in Bangladesh regarding BMW management. A descriptive correlational study was conducted from July 2019 to July 2020. Data were collected using validated questionnaires on sociodemographic characteristics, knowledge (14 items), and practices (13 items) related to BMW management. Statistical analyses, including descriptive statistics and bivariate analyses, were performed using SPSS. The study included 112 senior nurses with an average age of 29.26 years. Majority were female (88.4%) with basic B.Sc. or post basic B.Sc. education (59.8%). The nurses demonstrated varied levels of knowledge (low: 36.6%, moderate: 39.3%, high: 24.1%) and practices (low: 41.1%, moderate: 25.9%, high: 33.0%) regarding BMW management. A significant correlation was found with higher education level in both knowledge (p=0.024) and practice (p=0.049) levels. However, no significant correlations were observed based on age, sex, years of experience, or specific workplaces. The study highlighted gap in knowledge and practices among senior nurses regarding BMW management at the tertiary hospital. Targeted training programs and policy improvements are recommended to enhance BMW management practices, thereby reducing health risks and environmental impact associated with BMW.